Unraveling FOMO: Exploring the Factors Behind Fear of Missing Out among College Students - Zainita, Ulfi Hida; Anshari, Dien (Universitas Ahmad Dahlan, 2025)
The increasing use of social media among college students can trigger mental health problems such as FOMO (Fear of Missing Out). There are not many studies that look at the relationship between the intensity of social media use and FOMO in college students. This study aims to provide an overview of FOMO among college students and assess the factors associated with FOMO. This quantitative study used a cross-sectional design with purposive sampling. Data collection was conducted through an online survey filled out by 104 college students. The variables measured were respondent characteristics, duration of social media use, number of social media accounts, and FOMO scale. The results of this study showed that 73.1% of students were classified as high duration users, 77.9% had less than 10 accounts, and 43.3% had high FOMO. There was a significant relationship between age (p=0.003) and undergraduate program (p=0.001) with FOMO. This study also found the significant relationship between duration (p=0.012) and number of accounts (p=0.007) with FOMO. There was a significant relationship between age, undergraduate program, duration, and number of accounts with FOMO in undergraduate students.